Biochemical and molecular characterization of fluorescent Pseudomonas for potential of Pyricularia oryzae - Sharifi Noori, Mansoureh Sadat (2013)
The present study emphasizes on the isolation and characterization of strains of fluorescent Pseudomonas collected from rice plants obtained from different localities in Peninsular Malaysia. Genetic diversity of Pseudomonas isolates were determined using molecular markers, including 16S rRNA gene and Rep-PCR and the 16S ribosomal RNA gene sequences of selected plant growth-promoting rhizobacteria (TS3C4 isolate), and were analyzed for possible predictive gene/protein using molecular bioinformatic. Twenty strains employed in this study were initially isolated from rhizosphere of healthy rice plants from three states of Peninsular Malaysia (Penang, Malacca and Selangor). The isolates were purified and subjected to identification based on morphological and biochemical characters. Through biochemical and morphological characterization, these isolates were tentatively identified up to generic level. Following API 20NE biochemical identification kit of the 20 isolates, 16 strains were identified as Pseudomonas fluorescens, two isolates belong to the species of the P. luteola, one isolate to the P.putida and a single isolate (TS3C4) showed a doubtful identification. It was observed that different strains of bacteria produced various concentration of indole acetic acid. Overall, out of twenty isolates nineteen of them were able to form zone of solubilization on the NBRIP medium. Based on the dual culture assay study, results clearly indicated the potential of nineteen isolates to inhibit the Pyricularia oryzae, the causal agent of rice blast disease, while isolate TS3A1 did not show inhibitory activity against this fungus. The results indicated the ability of all the isolates to produce both HCN and siderophores. In addition isolates such as DL26, DL17, TS11, and TS3A2 showed significantly higher production of siderophores compared to other isolates. All twenty isolates were tested for production of protease enzyme but only six isolates i.e. TS3C8,TS3B5, TS3C4, TS25, TS11, and reference strain NCIM 2099 showed protease activity. Results from the greenhouse study for biocontrol activity of selected plant growth promoting rhizobacteria indicated that out of four strains tested (TS3B5, TS3C4, DL22,and NCIM 2099 as reference strain) for their bio-control potential against Pyriculariaoryzae in greenhouse, TS3B5, TS3C4 and NCIM 2099 exhibited 13.50% reduction in disease index whereas, isolate DL22 showed disease index reduction in the rang of 16.88% relative to control. Out of the four promising strains, TS3C4 emerged as the best organism in plant growth promotion and was selected for sequence analysis of 16s rRNA gene for prediction of useful gene/protein which may involve in plant growth promotion and biocontrol traits. Most of the isolates identified as Pseuodomonas fluorescens based on API 20NE kit, were clustered together (cluster B), while cluster A was divided into two sub-clusters which was identified as Pseudomonas aeroginosa. Cluster C contained two isolates characterized as Pseudomonas luteola. Surprisingly,the isolate TS3C4 showed doubtful identification by API 20NE kit, was placed in cluster D which was very distinct from the others. This spatial separation of isolate TS3C4 suggests that this strain might be another strain of rhizobacteria. The results of clustering of phylogeny tree with 16s rRNA gene sequencing showed that all the Malaysia isolates were classified in b1 subgroup, while similar strains from NCBI were placed in different group and sub-group. This research clearly demonstrated that Pseudomonas isolates originating from different geographic region in Peninsular Malaysia were phylogenetically similar to each other compared to similar strains from NCBI which were isolated from different country. In silico 16S rRNA gene sequence analysis of selected isolate TS3C4 was able to predict potential useful gene/protein from small open reading frames such as kinase, outer membrane ferric siderophore receptor, Chain X,1.8a Crystal Structure of the Pa2412, protease, 3-oxoacyl-ACP synthase III and carboxyl-terminal protease proteins which involved in biological control activity when composed with protein BLAST data bank. Although some of these secondary metabolites were confirmed through biochemical characterization, these approaches must be accompanied with in vivo evidences for validation of its beneficial mechanisms and characteristics.